VENDIAN-CAMBRIAN SEDIMENTARY PROVENANCE OF THE UPPER KALAR DEPRESSION (ALDAN SHIELD) ACCORDING TO GEOCHEMICAL DATA - S. I. Merenkova; I. N. Gromyak; D. N. Dogadkin; E. V. Karpova; R. R. Gabdullin; V. Yu. Vodovozov; T. G. Kuzmina (Геодинамика и тектонофизика, 2024)
There are presented the results of geochemical studies of the Vendian-Cambrian terrigenous rocks in the Upper Kalar depression– sandstones of the Silimkun formation, exposed in the floodplain of the Kilcheris River (left tributary of the China River), in the upper reaches of the Kemen River. The rocks are enriched in Sc, Cr, Nb, V, Co, Ni, as well as in Mo and heavy rare earth elements. This study demonstrates a rare pairwise correlation between Mo and Cr. A strong positive correlation of P with Nb, Ti and Fe is indicative of P sorption phenomena in alteration products of titanium minerals (e.g. leucoxene). It has been found that the sandstones of the Silimkun Formation were formed as a result of the destruction of granitoids of the Kalar massif – presumably granite porphyries and fine-grained porphyritic biotite granites. The influence of the gabbro-norites of the Chiney complex, enriched in trace elements commonly found in rocks, is less pronounced.